Improving the Performance of Bhabinkamtibmas to Prevent the Crime of Motor Vehicle Theft in the Jurisdiction of Mojosongo Police - Purba, Ernala (Advances in Police Science Research Journal, 2024)
Motor vehicle theft is the most frequent criminal offense in the jurisdiction of the Mojosongo Police Sector. Of course, the community is very concerned because every year the incidence of theft continues to increase. Therefore, the role of the Bhabinkamtibmas is needed to provide guidance and counseling (Bimluh) to the community about motor vehicle theft. This guidance is conducted so that the community understands how to secure their personal belongings and how to handle theft if it occurs in their environment. This paper uses qualitative research methods to discuss the issues related to optimizing guidance and counseling activities to prevent motor vehicle theft. The research location is in the jurisdiction of the Mojosongo Police Sector. This paper utilizes management theory and the concepts of Bhabinkamtibmas and Bimluh. Data analysis in this research uses interview results, observation, and documentation study